2018
DOI: 10.3349/ymj.2018.59.9.1057
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Insulin Resistance on Acetylcholine-Induced Coronary Artery Spasm in Non-Diabetic Patients

Abstract: PurposeCoronary artery spasm (CAS) and diabetes mellitus (DM) are implicated in endothelial dysfunction, and insulin resistance (IR) is a major etiological cause of type 2 DM. However, the association between CAS and IR in non-diabetic individuals has not been elucidated. The aim of the present study was to evaluate the impact of IR on CAS in patients without DM.Materials and MethodsA total of 330 eligible patients without DM and coronary artery disease who underwent acetylcholine (Ach) provocation test were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…The effects of insulin resistance on vascular biology include: 1) defects in glucose homeostasis, substrate oxidation, and mitochondrial function; 2) increased inflammation and oxidative stress; 3) alterations in lipids and lipoproteins; 4) impaired lipid storage in adipocytes via defects in both lipolysis and triacylglycerol synthesis; and 5) vasoregulation due to a reduction in endothelial nitric oxide synthase (eNOS) activity and nitric oxide (NO) production (110,(93)(94)(95)(96)(97)(111)(112)(113)(114)(115)(116). Insulin resistance is also positively associated with acetylcholine-induced coronary artery spasm in patients without frank T2D (117).…”
Section: Dysglycemia-based Chronic Diseasementioning
confidence: 99%
“…The effects of insulin resistance on vascular biology include: 1) defects in glucose homeostasis, substrate oxidation, and mitochondrial function; 2) increased inflammation and oxidative stress; 3) alterations in lipids and lipoproteins; 4) impaired lipid storage in adipocytes via defects in both lipolysis and triacylglycerol synthesis; and 5) vasoregulation due to a reduction in endothelial nitric oxide synthase (eNOS) activity and nitric oxide (NO) production (110,(93)(94)(95)(96)(97)(111)(112)(113)(114)(115)(116). Insulin resistance is also positively associated with acetylcholine-induced coronary artery spasm in patients without frank T2D (117).…”
Section: Dysglycemia-based Chronic Diseasementioning
confidence: 99%
“…Myocardial dysfunction was noted and vascular function was impaired in patients with IR. High HOMA-IR level was associated with a decrease in global longitudinal stress and an increase in arterial stiffness [ 30 ], and HOMAIR positively correlates with the development of coronary spasm during acetylcholine provocation test [ 31 ]. An association of IR with the severity of coronary artery disease in patients with coronary artery disease has been demonstrated as well [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…VED can increase the whole systemic peripheral resistance and afterload through peripheral effects and aggravate the cardiac function impairment through central effects such as myocardial ischemia and inducible nitric oxide synthase (iNOS)-induced damaging effects ( Penna et al, 2006 ). Nemoto et al (2019) found that impaired endothelial function results in severe coronary artery stenosis as well as plaque vulnerability, while chronic hyperglycemia aggravates VED, resulting in more diffuse coronary artery lesions and worse clinical outcomes ( Kang et al, 2018 ). Meanwhile, coronary heart disease and infarction are precipitants of acute HF, and VED under hyperglycemia is highly likely to cause acute HF and seriously increases cardiac mortality (Driscoll et al, 2017).…”
Section: Mechanism Of Treating T2dm Complicated With Hf Based On Insu...mentioning
confidence: 99%